Preamble time-division multiple access fixed slot assignment protocol for secure mobile ad hoc networks - Khalid Hussain Mohammadani; Kamran Ali Memon; Imran Memon; Nazish Nawaz Hussaini; Hadiqua Fazal (International Journal of Distributed Sensor Networks)
Mobile ad hoc networks are the “spontaneous networks” which create a temporary network in any place and any time without using any extra fixed radio device of a full infrastructure network. Each device in this network works as a router to develop end-to-end communication connections and move independently in any direction. Mostly, mobile ad hoc networks use the IEEE 802.11b protocol with carrier-sense multiple access with collision avoidance medium access control layer protocol for sharing a common medium among the nodes simultaneously. Due to this distributed medium, the routing and medium access control layer of the mobile ad hoc network are prone to attacks. Among several attackers, blackhole attacker is the dangerous one which causes the loss of all data packets of devices in the network. Efficient medium access control protocol designs in this respect play a key role in determining channel utilization, network delay, and, more importantly, network security. In the proposed work, preamble information is used with time-division multiple access medium access control. The preamble time-division multiple access uses time synchronization for each time slot and does not assign much time to the blackhole attacker due to a fixed time slot. As a result, blackhole is not stable in all communications and such an attack is effectively defended. Simulation results show that, in the presence of the blackhole attacker, carrier-sense multiple access with collision avoidance has a high packet loss ratio and low network throughput as compared to the proposed preamble time-division multiple access.